PERAN PUSAT STUDI PARIWISATA UGM DALAM RANGKA MENINGKATKAN PROFESIONALISME KERJA BIDANG PARIWISATA DAERAH ISTIMEWA YOGYAKARTA - , HANNIF ANDY AL ANSHORI, Pitaya S.E.T., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In Indonesia, tourism is projected as the largest foreign exchange earner while improving the welfare of the people. Social reality shows that tourism is a complex phenomenon, not just an activity which its main object is the service industries involving product management and market, but also a process of dialogue between the tourists and the local community as a guest host. Tourism development should be based on a passion for applying the principles of good governance, both among government, private and public. Management of tourism requires professionalism that includes not only the skills and knowledge, but also a consistent attitude toward the commitment to sustainable development. One of the institutions engaged to conduct technical guidance, training, and socialization of the program is the Center for Tourism Studies, Gadjah Mada University. On this basis, the authors wanted to find out the role of the Center for Tourism Studies UGM in an effort to improve the professionalism of tourism in Yogyakarta. Another purpose of this paper is to analyze the importance of professionalism in tourism and business Center for Tourism Studies UGM in enhancing professionalism in tourism. In addition, the authors used qualitative methods of data obtained based on the results of observations, interviews, participatory, and review of the literature to corroborate the results of research in PUSPAR UGM. Professionalism in tourism is a view or a mental attitude in the form of the commitment of the members of a profession to continue to reach and enhance the quality of profesionalism in the field of tourism. In performing its duties to enhance professionalism in tourism in DI. Yogyakarta, PUSPAR UGM is supported by much support from outside agencies both government and private. Moreover, in carrying out their duties, there are several barriers experienced PUSPAR UGM both internal and external of PUSPAR UGM, including the adjustment of time, less competent sources, and miss communication between agencies.